Trees and water: A survey of the perception and decisions of landowners in New Zealand - Grace B. Villamor; Meine vanNoordwijk; M. S. Srinivasan; Peter W. Clinton; Dean F. Meason (People and Nature)
Abstract Landowners' conceptualisation of the connection between trees and water matters for their land‐use decisions and the allocation of water resources in general. Tree–water interactions are commonly explored and explained through a biophysical lens where competing demands for water from other land uses, such as plantation forests and horticulture, are important. However, other values (positive or negative) can also play a role. Using a mixed method approach, we explored the key stakeholders' and landowners' perceptions of trees on farms and their interactions with water resources in three regions of New Zealand. Of the 363 surveyed participants, a large majority (70%) reported the presence of (exotic and native) trees on their farms. Landowners, composed of farmers and lifestyle block owners, were identified as direct actors influencing the landscape's socio‐hydrology, and most of them rely on natural water supplies for their farms. Our research reveals that issues relating to trees and their interaction with water—including climate change‐induced droughts, the effects of forest management and harvesting practices on water, and the decline in water quality—were raised by key stakeholders. Landowners chose to keep trees on their farms to enhance biodiversity, mitigate soil erosion and provide shelterbelts. They also value trees for shade for their livestock and for improving water quality. Our findings suggest that older landowners, those who perceive water quality as less concern and those who perceive lower flood risks are less likely to plant trees. This study sets the foundation for understanding the relationship between trees and water in New Zealand. However, additional research is necessary to assess the synergies and trade‐offs arising from the interactions of socio‐hydrological systems. Read the free Plain Language Summary for this article on the Journal blog.